Post-harvest handling, packaging and value addition protocols for mulberry - Gurjar, P S; Sarolia, D K; Berwal, M K; Surajbhan (Indian Horticulture, 2024)
Mulberry fruits are renowned for their taste, rich nutraceuticals and several health advantages. It is a potential premium fruit for fresh consumption and value addition. The major obstacles for its commercial cultivation and marketing are high perishability and very short post-harvest life. Protocols have been standardized for harvesting, post-harvest handling and packaging for safe storage, transport and marketing of fresh fruits. In addition, juice extraction, bottling, beverages preparation and dehydration methods were also developed at ICAR-CIAH, Bikaner.